A new, low-cost way to cut both corrosion and bacteria...Hercules "RADA" - Hercules Incorporated (1949 Hercules Advertisements, 1949)
Advertisement for "RADA," or rosin-amine-D-acetate, a water soluble chemical manufactured by the Hercules Powder Company for use as a corrosion inhibitor and to control bacteria in water flooding systems, among other applications. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Chemical industry; Water quality; Hercules Incorporated; Water purification chemicals industry; Corporations; Water; Water quality management; Advertising, Industrial